2007
DOI: 10.1177/154193120705100201
|View full text |Cite
|
Sign up to set email alerts
|

In-Flight Planning and Intelligent Pilot Aids for Emergencies and Non-Nominal Flight Conditions Using Automatically Generated Flight Plans

Abstract: The following study examined pilots' performance on in-flight planning tasks in non-nominal and emergency conditions using autoflight systems capable of automatically generating a flight plan. The findings revealed that autoflight systems did not significantly impact replanning, while the scenarios did significantly affect the primary performance measures of distance flown and time of flight. Additionally, pilots selected the most direct route when possible and did not distinguish between emergency and non-nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, Kaber et al (2009) also found that the use of high‐level automation led to significantly lower objective and subjective pilot workload responses. Still other studies have demonstrated the same workload advantage of high‐level (FMS‐based) cockpit automation in simulated critical event (flight replanning) scenarios (Kalambi et al, 2007). It is important to note here that, in some investigations of the effects of levels of cockpit automation on pilot performance, higher levels of automation have also provided pilots with less complex and more usable interfaces as compared with modes of low‐level automation, which may also contribute to reduced workload experiences.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, Kaber et al (2009) also found that the use of high‐level automation led to significantly lower objective and subjective pilot workload responses. Still other studies have demonstrated the same workload advantage of high‐level (FMS‐based) cockpit automation in simulated critical event (flight replanning) scenarios (Kalambi et al, 2007). It is important to note here that, in some investigations of the effects of levels of cockpit automation on pilot performance, higher levels of automation have also provided pilots with less complex and more usable interfaces as compared with modes of low‐level automation, which may also contribute to reduced workload experiences.…”
Section: Introductionmentioning
confidence: 81%
“…In general, when a pilot must replan a route because of either non‐nominal (e.g., runway closure or change, weather disturbance) or emergency (e.g., cargo fire, medical emergency, etc.) circumstances (Kalambi et al, 2007), there are required functions, including systems monitoring, generating decision alternatives, and selecting and implementing options. The functions actually performed by the pilot depend on the level of aircraft automation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, when a pilot must replan a route because of either non-nominal (e.g., runway closure or change, weather disturbance) or emergency (e.g., cargo fire, medical emergency, etc.) circumstances (Kalambi et al, 2007), there are required functions, including systems monitoring, generating decision alternatives, and selecting and implementing options. The functions actually performed by the pilot depend on the level of aircraft automation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Chen & Pritchett, 2001;Kaber et al, 2009;Kalambi et al, 2007;Wright, Kaber, & Endsley, 2003) has investigated the effect of various forms of cockpit automation on pilot performance and workload in replanning scenarios. The use of high-level automation for flight path control (e.g., the FMS) has been found to support superior piloting performance in advance of critical events, such as an approach revision (Chen & Pritchett, 2001;Wright et al, 2003).…”
Section: Introductionmentioning
confidence: 99%